Radionuclides and heavy metals in environment (Kluwer Academic Publishers, 2001)
The environment contains an abundance of man-made and natural radionuclides, as well as polluting heavy metals. Their accumulation and the inevitable adverse impact on human health is a matter for serious international concern. Such modern environmental problems are reviewed in an integrated fashion here.